2021
DOI: 10.1155/2021/6653677
|View full text |Cite
|
Sign up to set email alerts
|

The Formidable yet Unresolved Interplay between Endometriosis and Obesity

Abstract: Obesity and endometriosis are two very common entities, yet there is uncertainty on their exact relationship. Observational studies have repeatedly shown an inverse correlation between endometriosis and a low body mass index (BMI). However, obesity does not protect against endometriosis and on the contrary an increased BMI may lead to more severe forms of the disease. Besides, BMI is not accurate in all cases of obesity. Consequently, other anthropometric and phenomic traits have been studied, including body a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
1
19
0
6
Order By: Relevance
“…To date, there is convincing evidence for an inverse association of endometriosis and BMI [ 231 ]. Low overall adiposity and a preferred localization of fat below the waist were found to be related to endometriosis [ 232 ].…”
Section: Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is convincing evidence for an inverse association of endometriosis and BMI [ 231 ]. Low overall adiposity and a preferred localization of fat below the waist were found to be related to endometriosis [ 232 ].…”
Section: Endometriosismentioning
confidence: 99%
“…In later life, abdominal fat distribution contributes to the development of endometriosis [ 233 ]. Overweight/obesity is a risk factor for various diseases, and obesity as well as endometriosis are associated with low-grade inflammation and higher estrogens, and thus an inverse relation is exceptional [ 231 ]. Associations of endometriosis with body-fat distribution and metabolic diseases, such as insulin resistance, have not been resolved.…”
Section: Endometriosismentioning
confidence: 99%
“…Dziunycz et al obtained opposite results [ 10 ]. Based on the data on increased leptin and ghrelin levels in the PF, Pantelis et al suggested that endometriosis is associated with obesity, despite an obvious decrease in BMI in patients with endometriosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence highlights the multiple links between endometriosis and systemic diseases with immunologic and metabolic changes and has identified comorbidities associated with endometriosis such as autoimmune diseases, cancers, and cardiovascular disease [ 54 , 55 ]. Therefore, studies targeting biological substances that specifically function in both adipose tissue metabolism and endometriosis could help better understand the observed relationship between adiposity and the establishment or behavior of endometriosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on body mass index (BMI) and endometriosis have demonstrated mixed results. There is evidence of an inverse correlation between endometriosis and BMI, and obesity is often associated with a lower incidence of endometriosis [ 23 , 24 , 25 , 26 ]. In a meta-analysis of studies on BMI and endometriosis from 2019, lower BMI increases the relative risk of endometriosis.…”
Section: Introductionmentioning
confidence: 99%